DIGITAL MARKETING AND PRODUCT QUALITY ON CUSTOMER SATISFACTION - Narto, Eko; Hotimah, Usnul (Digital Business Journal, 2024)
This research aims to analyze the influence of digital marketing (X1) and product quality (X2) on customer satisfaction (Y) in the study of Tuh coffee shop consumers. This research is quantitative research and survey research. The sample taken in this research was 96 respondents. Data was obtained from distributing questionnaires. Primary data processing uses MS.Excel and Statistical Package For Social Science (SPSS) version 26 as evaluation. Meanwhile, the data analysis used in this research includes: descriptive statistical analysis, validity test, classical assumption test, linear regression analysis, correlation analysis, coefficient of determination test and hypothesis test. The results of this research show that the variables Digital Marketing (X1) and Product Quality (X2) simultaneously have a positive and significant effect on Customer Satisfaction (Y) as indicated by the Fcount>Ftable value, which is 8,382 > 2.70 with a significant value of 0.000 <0.05 .